Impacts of Anti-TNF Treatment on Improvement in Work Place and Household Productivity in Patients with Psoriatic Arthritis - Karadag, Omer; Dalkilic, Ediz; Onat, Ahmet Mesut; Kucuksahin, Orhan; Kasifoglu, Timucin; Kisacik, Bunyamin; Kalyoncu, Umut (Wiley, 2016)
[Abstract Not Available]
Annual Meeting of the American-College-of-Rheumatology/Association-of-Rheumatology-Health-Professionals (ACR/ARHP) -- NOV 11-16, 2016 -- Washington, DC